The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15587/1729-4061.2015.38779
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring algorithm of two-factor authentication method based on рasswindow system

Abstract: Кандидат технических наук, доцент Кафедра информационных систем Харьковский национальный экономический университет им. С. Кузнеца пр. Ленина,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In [2], it is shown that network simulations for effective use should include highly accurate models of users, intruders and/or defenders. Simulations can be used to implement scripts for learning war games with realistic traffic and usergenerated vulnerabilities.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In [2], it is shown that network simulations for effective use should include highly accurate models of users, intruders and/or defenders. Simulations can be used to implement scripts for learning war games with realistic traffic and usergenerated vulnerabilities.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…A special place among the mechanisms of EA is occupied by two-factor authentication methods based on various smart cards, USB keys, OTP passwords [9,10,[12][13][14]. Multi-factor authentication methods have become widespread among hi-tech organizations, financial and insurance sectors of the market, large banking institutions, and public sector enterprises.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…However, the studies of this method and the proposed monitoring algorithm [12] allow hacking the Passwindows system in 3-5 sessions by forming a bar code of the u card of the user of banking services. Fig.…”
Section: Authentication Level 1 (Aal1)mentioning
confidence: 99%
“…These changes contribute to the development of the digital economy, and in particular, electronic banking [1,2]. However, this is accompanied by an increase in the number and diversity of cyber threats.…”
Section: Introductionmentioning
confidence: 99%
“…third criterion). Thus, as statistical indicators for assessing collision properties, use[54]:-mathematical expectations m(n 1 ), m(n 2 ) and m(n 3 ) of maxima of the number of hashing rules (MAC formation rules) at which equalities (1),(2) and(3)are satisfied, respectively; -dispersion D(n 1 ), D(n 2 ) and D(n 3 ), characterizing the dispersion of the values of the number of hashing rules (MAC formation rules), at which equalities (1),(2) and(3)are satisfied, with respect to their mathematical expectations m(n 1 ), m(n 2 ) and m(n 3 ), respectively.…”
mentioning
confidence: 99%